2019
DOI: 10.1183/23120541.00013-2019
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural interventions targeting physical activity improve psychocognitive outcomes in COPD

Abstract: This study explored the impact of a self-management behaviour modification (SMBM) programme with/without bronchodilators and with/without exercise training (ExT) to improve daily physical activity on psychological and cognitive outcomes in COPD patients as a secondary analysis of the PHYSACTO trial.A 12-week, four-group, randomised, partially double-blind, placebo-controlled, parallel-group trial of SMBM in addition to tiotropium 5 µg, tiotropium/olodaterol 5/5 µg, tiotropium/olodaterol 5/5 µg plus ExT, or pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…This may be related to psycho-cognitive factors such as anxiety and depression or even socio-cultural status and educational level [22,23]. There is also a complex interaction between the healthcare professional"s communication and the patient.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to psycho-cognitive factors such as anxiety and depression or even socio-cultural status and educational level [22,23]. There is also a complex interaction between the healthcare professional"s communication and the patient.…”
Section: Discussionmentioning
confidence: 99%
“…clinically stable settings [48], or with much different 6-minute walking distances. Further studies should clarify the effects of factors leading to a reduction in depression, including medical and psychotherapeutic interventions [56], as well as physical activity, exercise and rehabilitation [57][58][59][60], which may also influence test results and may in parallel improve the quality of life and possibly the outcome of COPD patients [47].…”
Section: Discussionmentioning
confidence: 99%
“…83 Lavoie et al also found that anxiety and depression reduced with increases in either physical activity or exercise capacity, and cognitive function improved with increased exercise capacity in COPD patients. 84 Moreover, exercise Figure 1 The possible mechanism of exercise improving cognitive impairment in the elderly with COPD. Abbreviations: NE, norepinephrine; DA, dopamine; 5-HT, 5-hydroxytryptamine; IL-10, interleukin-10; IL-6, interleukin-6; CRP, C-reactive protein; TNF-α, tumor necrosis factor-α; PaO2, partial arterial blood oxygen pressure; PaCO2, partial arterial carbon dioxide pressure; VEGF, vascular endothelial growth factor; IGF-1, insulin-like growth factor-1.…”
Section: Possible Mechanism Of Exercise On the Improvement Cognitive mentioning
confidence: 99%